Gender Discrimination, Competition and Efficiency. Issue 2 (December 2022) - Marjit, Sugata; Ray, Moushakhi
The standard literature on discrimination in labour market discusses discrimination-generated inefficiency at the firm level which cannot be sustained under competition. As competition gets intense, firms would be more disciplined and would be forced to refrain from practising discrimination. This forms the core of the pioneering works by Becker (1957) and Arrow (1973). In this article, we argue that when firms are heterogeneous in terms of productivity, some of the more efficient firms can easily survive practising discrimination and only relatively inefficient firms will quit the market. Thus, incentives to discriminate, if any, would be greater for more efficient firms. Once they survive, measured efficiency of the market would, in fact, increase. Thus ironically, discriminating industries would exhibit higher efficiency. This article shows that, in a model with heterogeneous firms, a competitive market system cannot eliminate the problem of discrimination. Thus, competition and discrimination may coexist.